Optimization of the Alumni Site of SMK Muhammadiyah Sintang - Ponti Harianto; Bella Anjella Metalya; Aditya Widman Putra (JUDIMAS, 2020)
Alumni have an important role in the development of educational institutions in the public sphere, but regarding alumni, many schools have not used alumni in school contributions, one of which is SMK Muhammadiyah Sintang. Regarding information, SMK Muhammadiyah alumni have not implemented an online alumni data collection and management system. So far, data collection on alumni is still carried out by recording in written documents which results in data management that cannot be done quickly, and errors often occur, and it is difficult to update information about alumni. In conducting research, the authors use existing literature and literature study materials to build alumni websites using the WSDM (Website Development Design Method) research method, website development methods using Extreme Programming (XP), and the development of alumni information systems using a bootstrap framework, providing designs responsive web that gives the appearance of the website will automatically adjust the screen size of the browser used. The purpose of this research is to design or create a website that can help schools quickly and accurately in the process of data collection and data management of alumni in obtaining information about alumni.